The Conceptual Foundations of the Formation of an Ecosystem of Innovations in Agribusiness - Kyfyak Viktoriia I. (Problemi Ekonomiki)
The article is devoted to the development of theoretical foundations and practical mechanisms necessary for the creation and development of an innovation ecosystem in the agrarian sector of Ukraine, focusing on the key determinants that are decisive for the integration of new technologies into the industry. The purpose of the study is to substantiate the conceptual foundations of the formation of such an ecosystem, which would include a multi-level structure, where the central role is played by synergistic interaction between the State institutions, business, and scientific structures. In this context, the article proposes a multi-vector approach that takes into account the peculiarities of institutional support, private initiatives, as well as the impact of education and science on the development of agrarian innovations. Considerable attention is paid to the analysis of the report «European Innovation Scoreboard 2024: Country Profile Ukraine», which allows to identify specific trends and opportunities for further research and improvement of innovative approaches in the agrarian business of Ukraine. An analysis of the current challenges faced by agribusiness in the context of global economic and climatic fluctuations is presented, and strategic solutions to maintain the competitiveness of the Ukrainian agrarian business at the international level are proposed. Foreign experience is analyzed, in particular Israel’s success in introducing innovations in the agrarian sector, based on increased digitalization, environmental sustainability and new market strategies. The prospects for adapting these approaches to Ukrainian conditions to ensure sustainable development of the agricultural sector are also considered. An important aspect of the study is to identify areas that allow creating an integrated model of the innovation ecosystem, which takes into account the specifics of the agrarian sector and national characteristics. This mechanism will contribute to the effective implementation of innovations in the production processes of agribusiness, ensuring its sustainable development in the face of long-term fluctuations, in particular, such as war.